Aparicita tīrthāṭanaṅṅaḷ : Pāṇḍavapuraṃ paṭhanaṇṅaḷ - Surēṣ, En. Bi. (Vilayur P.O., Palakkad Dt., Kerala : Lōgōs Buks, 2020)
Studies on a Malayalam novel.
In Malayalam.
Keywords: Sētu, -- 1942-; Malayalam fiction -- History and criticism